Mothers' stories of loss: their need to be with their dying child and their child's body after death - Ruth Davies (Journal of Child Health Care, 2005)
Children die annually worldwide from a range of life-limiting conditions.The majority in the UK will die in hospital as only a minority die at home or inchildren’s hospices. There is a paucity of research exploring the experiencesof mothers whose children die in such settings and even thought the need forthem to be in a caring and supportive environment would seem self-evident, as thisqualitative study finds, sadly this is not always provided. Interviews with 10 mothersenabled comparisons to be made between the care and support received inhospital, at home and in a children’s hospice. Mothers' stories identified theirneed for time, space and privacy with their dying child and their child’sbody after death. Memories of these events continued to affectthem, giving further support to new theoretical understandings of parentalgrief which suggest that parents maintain continuing bonds with their deadchild by preserving memories and recollections of their life and death.